Real-World Distributed Computer with Ibis. - Bal, Henri E.; Maassen, Jason; van Nieuwpoort, Rob V.; Drost, Niels; Kemp, Roelof; Palmer, Nick; Kielmann, Thilo; Seinstra, Frank; Jacobs, Ceriel (Computer (00189162), 2010)
The use of parallel and distributed computing systems is essential to meet the ever-increasing computational demands of many scientific and industrial applications. Ibis allows easy programming and deployment of compute-intensive distributed applications, even for dynamic, faulty, and heterogeneous environments.